Factors Influencing The Digital Transformation Of Non-Financial Companies - Anton; Yusia Bela; Joseph Hendryawan Krisantanu Splendid; Henny Setyo Lestari; Farah Margaretha Leon (Jurnal Ekonomi, 2024)
Digital revolution driven by the rapid progress of internet technology has swept across the world. This changed the socio-economic landscape and ushered in a new era of industrial and technological transformation. This wave of digitalization has fueled dynamic economic activities and profoundly impacted global corporate innovation. This study investigates whether factors such as enterprise size, capital structure, percentage of accounts receivable, management overhead ratio, profitability, ownership, business age, and growth affect digital transformation. The samples used in this research is the financial statements of companies listed during the year of 2020 to 2023. The number of samples selected is 42 companies with 168 data. The results of this research indicated that percentage of accounts receivable, management overhead ratio, profitability, ownership, business age, and growth have an influence on digital transformation, while enterprise size and capital structure have no effect on digital transformation.